WEB BASED E VOTING TRAINING FOR STUDENT COUNCIL CHAIRMAN ELECTION AT HIGH SCHOOL - Nofrima, Sanny; Melinda, Melinda; Fitriyanti, Emiliy (Universitas Djuanda, 2023)
Implementation in the process of electing the student council president involves information technology using the electoral system as learning for students who practice democracy directly. Activities, especially the election of the Student Council chairperson, still use media assisted by simple information, namely in the form of sheets of paper, and are still not effective. The problem faced requires a new motivation that is easier to guide information on the election of the Student Council chairperson in Palembang City Senior High School as well as minimizing information fraud in the election and facilitating the election of the Student Council chairperson. This study introduces the E-Voting Website to Student Council Palembang City by bringing up the idea of implementing the Student Council chairman election by utilizing development information.